A pilot study compare the efficacy of amlodipine and captopril in the treatment for hypertensive urgency emergency department and primary care clinic Hospital Universiti Sains Malaysia - Chia Boon, Yang (2008)
To compare the efficacy of amlodipine and captopril in the treatment for hypertensive urgency. Methodology This is an open labeled randomized prospective control study with blinded end point conducted from Oct 2006-Sept 2007. Patient aged> 18-year-old with persistent elevated BP> 180/110 mmHg after 30 min bed rest was included in the study. Patient who allergic to study drugs, with target organ damage (acute coronary syndrome, CVA, CRF), elevated blood sugar >20mmolll, pregnancy or breast feeding was excluded. Patients were randomized using block randomization into amlodipine group (Amlodipine 5 mg) and captopril group (Captopril 25 mg). Single NIBP machine was used to monitor BP and PR hourly for 4 hours, subsequently 4 hourly until 16th hour of medication. If target BP not achieved at 4th hour of medication, Chlorothiazide 250 mg was added. Result 28 patients enrolled in the study, 18 patients in amlodipine group and 10 patients in captopril group. Mean age for amlodipine group was 60.2 years old (sd 13.02) and 45.0 years old (sd 14.73) for captopril group, p=0.046. Mean SBP on admission was 206.9 xiii mmHg (sd 27.16) for amlodipine group compared to 198.4 mmHg (sd 14.32) for captopril group, p=0.487. SBP at 1st hour was significantly difference with p=0.004. The SBP reduced gradually from 2nd to 161h hour, with no significant difference. DBP on admission was significantly difference (p=0.009) with mean at 112.4 mmHg (sd 9.47) in amlodipine group and 124.2 nunHg (sd 1 0.17) in captopril group. However, the differences in DBP were not significant throughout the study. The mean MAP on admission was 143.9 nunHg (sd 9.27) in amlodipine group compared to 148.9 mmHg (sd 7.75) in captopril group, p=O.l37. The differences in MAP and PR between study groups were not significant. Conclusion Amlodipine is comparable to captopril in the treatment of hypertension urgency. Keywords Hypertensive urgency; Emergency department; Amlodipine; Captopril